An improved Pareto distribution for modelling the fault data of open source software. (23rd July 2013) - Luan, Shao‐Pu; Huang, Chin‐Yu
SUMMARY In the modern society, software plays a very important role in many application systems. Consequently, the main goal of project managers and software engineers is to deliver reliable software within very limited resource, time and budget during the software development life cycle. Presently, it is widely recognized that open source software (OSS) has developed as a new (and novel) form of both personal and aggregation production. In the past, some research has shown that the traditional Pareto distribution (PD) and the Weibull distribution models can be used to describe the distribution of software faults of OSS. However, there could be a negative value for the cumulative probability of the traditional PD model in some cases. In this paper, based on our past studies, a modified Pareto‐based distribution model, called the single‐change‐point 2‐parameter generalized PD (SCP‐2GPD) model is proposed. The method of choosing an appropriate change‐point is presented and illustrated. Some mathematical properties of the proposed model are also discussed. Experiments are conducted using several real OSS data, and evaluation results show that our proposed SCP‐2GPD model depicts the real‐life situation of the software development life cycle more faithfully and accurately. Copyright © 2013 John Wiley & Sons, Ltd.